Penerapan permainan tradisional melalui pendekatan konseling eklektik untuk mengembangkan keterampilan sosial anak usia dini - Fitriyanti, Evi; Satrianta, Hengki; Utami, Sri (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
This study aims to obtain an overview of the effectiveness of the application of traditional games through an eclectic counseling approach to develop early childhood social skills in the B class of Kindergarten Fajar. The research method used is Classroom Action Research (CAR), in order to improve the learning process to be able to develop early childhood social skills by applying traditional games through an eclectic counseling approach. CAR was conducted in three cycles, each cycle carried out through two meetings, with the subject of early childhood in the class B class of Fajar Kindergarten, amounting to 13 children. The results showed that there were changes in children's social behavior with increased social skills possessed after the implementation of traditional games through an eclectic counseling approach in the learning process.